Síntese enzimática de éster do biodiesel a partir de lipases fúngicas de Penicillium sumatrense produzidas por fermentação no estado sólido - Krüger, Cíntia (2017)
The objective of this study was to produce the lipase of Penicillium sumatrense by solid-state fermentation (SSF), in this manner taking advantage of agroindustrial residues for the production of an enzyme that is useful in biocatalysis. It was studied as a substrate, the agroindustrial residue, crambe cake (Crambe abyssinica hochst), provided by MS Foundation, Mato Grosso do Sul. The enzymatic activity was determinated by the titrimetric method, using olive oil as substrate. In order to optimize the lipase production, was performed an experimental design 22, aiming to evaluate the effects of the variables involved in the process (substrate granulometry and moisture). The response variable chosen was the enzymatic activity in U (Total Units), of each fermented enviorement. Statistical analyzes were performed by the software Statistica 7.0. The results of the experimental design indicated that the enzymatic activity was maximum (243,0 U) when using a substrate moisture of 60 % (m/m, wet basis), substrate granulometry of 28 mesh, 29°C, after 96 h of fermentation. The dry fermented solid produced from the industrial waste crambe cake (24,3 U gss-1) was used in the synthesis studies of ethyl oleate in n-heptane studying the variables temperature and molar ratio (MR, acid:alcohol). The ester yield was evaluated by the method of LowryTinsley. The best conditions for ester production were 37C, MR of 1:3 and the amount of enzyme in the reaction of 60,0 U, obtaining a yield or conversion in ester of 100,0% after 30 min of reaction. It was also found that the time required to reach equilibrium was 40 min. The crambe cake was reused 10 times for the synthesis reaction of ethyl oleate. In the sixth reuse the enzyme reached half of the yield initially obtained (half life time). The results obtained in this work are inedited, since no papers were found in the literature using lipase of Penicillium sumatrense produced by solid-state fermentation with applications in biocatalysis and show the feasibility of using fermented solids directly in reactions of ester synthesis in organic solvents. Key-words: enzymes; SSF; ethyl oleate.